EVALUASI KINERJA SIMPANG BERSINYAL DENGAN PENDEKATAN PKJI 2023 DAN PTV VISSIM (Studi Kasus: Simpang Wisnu Murti Kabupaten Tabanan) - I Made Kariyana; Tri Hayatining Pamungkas; Lustomo Sepriyanto (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2026)
The Wisnu Murti Intersection in Tabanan Regency is a four-legged signalized intersection with three phases and a central roundabout. It serves as a primary connector between the Denpasar–Gilimanuk National Road and Ngurah Rai–MH Thamrin Road. Congestion and delays, particularly during peak hours, highlight the need to evaluate its performance and traffic signal control system. This study aims to assess the existing performance of the intersection using the Indonesian Highway Capacity Manual (PKJI 2023) and PTV Vissim microsimulation, employing indicators such as queue length, delay, and Level of Service (LOS). The analysis revealed poor performance, with a degree of saturation (Dj) of 1.37 and an average delay of 120.9 seconds/pcu (LOS F). Vissim simulation results showed the longest queue occurred on the east approach, reaching 436.34 meters with an average delay of 85.17 seconds/pcu. A recommended signal control scenario applying the early cut phase with a 113-second cycle significantly improved performance, reducing queue length by 69.9% and average delay by 60.6%. Adaptive green time distribution across phases provided better efficiency compared to the scenario without early cut. Therefore, the application of the early cut strategy is considered flexible, responsive to fluctuating traffic flow, and feasible for implementation at the Wisnu Murti Intersection.